Intramural Ventricular Septal Defect Is a Distinct Clinical Entity Associated With Postoperative Morbidity in Children After Repair of Conotruncal Anomalies - Patel, Jyoti K.; Glatz, Andrew C.; Ghosh, Reena M.; Jones, Shannon M.; Natarajan, Shobha; Ravishankar, Chitra; Mascio, Christopher E.; Spray, Thomas L.; Cohen, Meryl S. (Circulation (New York, N.Y.), 2015)
BACKGROUND—Intramural ventricular septal defects (VSDs) are interventricular communications through right ventricular free wall trabeculations that can occur after repair of conotruncal anomalies. We assessed the prevalence of residual intramural VSDs and their effect on postoperative course. METHODS AND RESULTS—Children who underwent biventricular repair of a conotruncal anomaly from January 1, 2006, to June 30, 2013, and had a postoperative transthoracic echocardiogram were included. Images were reviewed for residual intramural or nonintramural VSDs. The primary outcome was a composite of mortality, extracorporeal membrane oxygenation use, and need for subsequent catheter or surgical VSD closure. The secondary outcome was postoperative hospital length of stay. A residual VSD was present in 256 of the 442 subjects (58%), of which 231 (90%) were <2 mm in size. Forty-nine patients (11%) had intramural VSDs, and 207 (47%) had nonintramural VSDs. Patients with intramural VSDs were more likely to reach the primary composite outcome compared with those with nonintramural VSDs or no residual VSD (14 of 49 [29%] versus 15 of 207 [7%] versus 6 of 186 [3%]; P<0.0001). In addition, those with intramural VSDs had longer postoperative hospital length of stay compared with those with nonintramural VSDs or no residual VSD (20 days [interquartile range, 11–42 days] versus 7 days [interquartile range, 5–14 days] versus 6 days [interquartile range, 4–11 days]; P=0.0001). These associations remained significant after adjustment for known risk factors for poor outcomes, including residual VSD size and operative complexity. CONCLUSIONS—Among residual VSDs after repair of conotruncal anomalies, intramural VSDs are uniquely associated with postoperative morbidity, mortality, and longer postoperative hospital length of stay. It is important to recognize intramural VSDs in the postoperative period.